A pH-Triggered antibacterial and lubricating dual-function hydrogel coating for infection-resistant urinary catheters - Cheng, Ming; Lin, Weijie; Yu, Jianbo; Gao, Peiliang; Shi, Fange; Wang, Chunyu; Ma, Yong; Liu, Zhongdi; Dong, Guiying (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionUrinary catheterization frequently causes urinary tract infections and patient discomfort. While hydrogel coatings combining antibacterial and hydrophilic properties offer a potential solution, challenges such as uncontrolled antimicrobial release and poor coating adhesion limit their clinical utility. This study aimed to develop a novel dual-function hydrogel coating with controlled antibacterial activity and sustained lubrication for infection-resistant urinary catheters.MethodsA bilayer PL@SAMT/Mg coating consisting of an inner polydopamine layer loaded with the antimicrobial peptide LL-37 and an outer pH-responsive MgO@AAm/SA/TA hydrogel was fabricated via surface modification and UV crosslinking. The coating was applied to catheters via surface modification followed by UV-induced crosslinking. It was characterized using SEM, EDS, FTIR, rheometry, and friction tests. Its antibacterial efficacy was evaluated against Staphylococcus aureus and Escherichia coli at different pH levels. Cytocompatibility was assessed using CCK-8, live/dead staining, and ELISA assays with L929, SV-HUC-1, and RAW264.7 cells. In vivo biocompatibility and antibacterial performance were investigated using a rat subcutaneous implantation model.ResultsThe PL@SAMT/Mg coating exhibited a uniform, adherent bilayer structure with stable mechanical properties. It delivered excellent hydration lubrication and demonstrated pH-responsive swelling behavior. The release of LL-37 was sustained, while MgO release was significantly accelerated under alkaline conditions mimicking infection. The coating showed strong, pH-enhanced antibacterial activity against both S. aureus and E. coli. In vitro assays confirmed excellent cytocompatibility, anti-inflammatory effects, and anti-adhesion properties. In vivo, the coating minimized inflammation and significantly reduced bacterial colonization compared to uncoated catheters.DiscussionThe PL@SAMT/Mg coating successfully integrates intelligent antibacterial function with sustained lubrication. The PDA layer enables long-term preventive release of AMPs, while the pH-responsive hydrogel layer provides on-demand MgO release during infection. This synergistic, controlled-release strategy mitigates biotoxicity and resistance risks. The coating addresses key limitations of existing technologies through robust adhesion, effective antibacterial action, and biocompatibility, offering a promising approach to improve catheter performance and patient comfort.